Synergistic effect of three-dimensional cobalt diselenide/carbon nanotube arrays composites for enhanced hydrogen evolution reaction. (20th September 2018) - Zhang, Mingyuan; Hu, Aiping; Liu, Zheng; Xu, Yali; Fan, Binbin; Tang, Qunli; Zhang, Shiying; Deng, Weina; Chen, Xiaohua
Abstract: Three-dimensional CoSe2 /carbon nanotube arrays (CoSe2 /CNTAs) composite with optimized morphology has been synthesized through a microwave-thermal treatment-selenization method. The CoSe2 nanoparticles with an average size of ∼25 nm are anchored uniformly on the surface of CNTAs. The CoSe2 /CNTAs composite exhibits excellent hydrogen evolution reaction (HER) performance in an acidic electrolyte with a low Tafel slope of 36.7 mV/dec, a potential of −204 mV vs RHE at 10 mA/cm 2 and especially a low overpotential of 229 mV at a high current density of 100 mA/cm 2 . The high electrocatalytic activity can be achieved by the synergistic effect of CoSe2 nanoparticles and CNTAs. The CoSe2 catalyst particles with nanoscale size provide abundant active sites for HER. The CNT arrays possess well-ordered 1D conductive paths, providing a fluent charge transport channel for CoSe2 catalyst nanoparticles and external electrodes. Meanwhile, CNTAs with aligned intertube spacing can provide sufficient space for the penetration of electrolyte, rapid transport of ions (H + ) and release of produced H2 . Thus even at a high current density, the hydrogen evolution reaction can proceed smoothly. Graphical abstract: An integrated structure of three-dimensional CoSe2 /carbon nanotube arrays (CoSe2 /CNTAs) composite was synthesized through a microwave-assisted selenization method. The CoSe2 /CNTAs composite displays greatly improved performance in comparison with pure CoSe2 and CoSe2 /CNTs. Image 1 Highlights: CoSe2 /CNTAs composite was synthesized via a microwave-thermal treatment-selenization method. Such a composite shows the synergistic effect of CoSe2 nanoparticles and CNTAs with well-ordered conductive paths and aligned intertube spacing. The CoSe2 /CNTAs composite exhibits a low Tafel slope and a small overpotential at a high current density.